Monopelopia caraguata (Chironomidae: Tanypodinae: Pentaneurini) and Phytotelmatocladius delarosai (Chironomidae: Orthocladiinae) : Two Phytotelmatous Chironomids Distributed from Florida to Argentina - Siri, Augusto (2014)
Fil: Siri, Augusto. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Instituto de Limnología Dr. Raúl A. Ringuelet; Argentina